Introducing SEARCHBreast: a virtual resource to facilitate sharing of surplus animal material developed for breast cancer research - Morrissey, Bethny (NPJ Breast Cancer, 2016)
Animals studies have made significant contribution to expanding our knowledge of breast cancer. Often material is leftover and archived. SEARCHBreast provides a platform for collaborative sharing of archived material via a dedicated on-line database whereby users can both share and search available tissue. The SEARCHBreast database has information on over 50 different mouse models, including tissue from PDX models, available to share. With thousands of samples freely available, SEARCHBreast should be the first point of call for any researcher looking for animal material to aid their breast cancer research.